Pelatihan Pemasaran Produk Usaha Mikro Kecil Dan Menengah (UMKM) Berbasis Digital Di Kecamatan Citeureup - Guruh Herman Wasan; Anita Sariningsih (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2021)
Technological innovation in marketing by utilizing the internet in the form of digital marketing or internet marketing is a paradigm that must be understood in today's business, especially the MSME sector. The MSME sector contributed to the GDPof Bogor Regency reaching 28.45 percent in 2018. Community service activities in the form of marketing training for digital-based MSME products aim to find out the use of marketing media in MSMEs and increase knowledge and skills in using digital technologyfor MSME actors in Citeureup District. The methods used are observation, interviews, questionnaires, training and evaluation of training activities. The results of observations, interviews, and questionnaires show that there is still a lack of literacy indigital technology in product marketing due to a lack of knowledge and skills in using digital technology (social media/marketplace). The results of training activities and evaluation of training activities are known to increase the knowledge and skills of MSME actors in utilizing digital technology (social media/marketplace) as a means of product marketing to increase the absorption of MSME results. This community service activity is very useful for MSME actors in Citeureup District to increase the competitiveness of MSME products.